2012
DOI: 10.1074/jbc.m112.347484
|View full text |Cite
|
Sign up to set email alerts
|

Tetrameric Structure of the GlfT2 Galactofuranosyltransferase Reveals a Scaffold for the Assembly of Mycobacterial Arabinogalactan

Abstract: Background: GlfT2 is a bifunctional galactofuranosyltransferase essential for mycobacterial cell wall biosynthesis. Results: Crystal structures of free and UDP-bound GlfT2, along with mutagenesis and kinetic studies, reveal novel details underlying substrate binding and catalysis. Conclusion:The homotetrameric architecture, distinctive nucleotide-binding site, and unprecedented structural features underlying the bifunctional polymerase activity of GlfT2 are revealed. Significance: Novel insights into polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 53 publications
(75 reference statements)
2
87
0
2
Order By: Relevance
“…We confirmed the PMf association of six proteins by density gradient fractionation and performed further analyses on GlfT2, Ppm1, and PyrD. GlfT2 does not contain predicted TM domains, but rather, its crystal structure implies peripheral membrane association (40). Extending previous studies showing that GlfT2 cofractionates with both membrane and CW (24), our data demonstrated stable and specific binding of GlfT2 to the PMf membrane.…”
Section: Discussionsupporting
confidence: 83%
“…We confirmed the PMf association of six proteins by density gradient fractionation and performed further analyses on GlfT2, Ppm1, and PyrD. GlfT2 does not contain predicted TM domains, but rather, its crystal structure implies peripheral membrane association (40). Extending previous studies showing that GlfT2 cofractionates with both membrane and CW (24), our data demonstrated stable and specific binding of GlfT2 to the PMf membrane.…”
Section: Discussionsupporting
confidence: 83%
“…Apart from being a bifunctional GalT, GlfT2 displays additional interesting features: By using a substrate tethering mechanism, it is able to have intrinsic control of the chain length of the galactan product (May et al 2009). Further structural analysis of GlfT2 using X-ray crystallography and NMR has shed further light on how this unique enzyme is tetrameric and is able to control chain length processivity and bifunctionality using a single active site (Szczepina et al 2009;Wheatley et al 2012). …”
Section: Galactan Biosynthesismentioning
confidence: 99%
“…Of all the structure templates surveyed, the bestthreaded positional or conformational fit was with UDP-GALACTOFURANOSYL TRANSFERASE2 (GalfT2; PDB code 4FIX; Wheatley et al, 2012). The sequence-structure comparison threaded with FUGUE (Shi et al, 2001) gave an identity of 14% between RGP2 and 4FIX (Supplemental Table S2).…”
Section: Protein Modeling Indicates That the Mur5 Mutation Impacts Prmentioning
confidence: 99%
“…Improvements in sequencing technologies have reduced the years required to complete the reference genome of Arabidopsis (Arabidopsis Genome Initiative, 2000) to only days needed to assemble the genomes of hundreds of Arabidopsis ecotypes from extensive numbers of short-read sequences (Schneeberger . RGP2 threaded to GalfT2 (PDB code 4FIX_A; Wheatley et al, 2012). The model preserves the classical nucleotide-binding fold and places Cys-252 and Cys-257 on the face distal to the catalytic residues.…”
Section: High-throughput Sequencing Accelerates Mutant Identificationmentioning
confidence: 99%
See 1 more Smart Citation